Effect of Chickpea Protein Isolate on Gel Quality of Salt-reduced Liaoning Zhuanghe Big Bone Chicken Meatball - Ruichi YAN; Na JIN; Yuhong SU; Caimei SHAO; Hongli SHANG (Shipin gongye ke-ji)
To explore the effects of different proportions (1%, 2%, 4%) of chickpea protein isolate (CPI) on the gel quality of salt-reduced big bone chicken meatballs. The texture properties, color, water distribution, rheological properties and microstructure of salt-reduced big bone chicken meatballs in different treatment groups were determined. The results showed that the hardness, elasticity and chewability of salt-reduced big bone chicken meatballs in (1.4%NaCl, 4%CPI) treatment group were significantly higher than those in other treatment groups (P<0.05). Low-field NMR analysis showed that the big bone chicken meatballs with 4% CPI had the highest P21 and the lowest P22, which proved that the salt-reduced big bone chicken meatballs had the best water retention under this condition. Rheological characteristics showed that (1.4%NaCl, 4%CPI) treatment group had the largest energy storage modulus and the best elasticity. Scanning electron microscopy showed that compared with other treatment groups, the structure of big bone chicken meatballs gel treated with (1.4%NaCl, 4%CPI) was more compact and better continuity. In summary, the addition of 1.4%NaCl and 4%CPI is conducive to improving the gel quality of CPI salt-reduced big bone chicken meatballs.